2021
DOI: 10.3390/molecules26061663
|View full text |Cite
|
Sign up to set email alerts
|

Stretching of Bombyx mori Silk Protein in Flow

Abstract: The flow-induced self-assembly of entangled Bombyx mori silk proteins is hypothesised to be aided by the ‘registration’ of aligned protein chains using intermolecularly interacting ‘sticky’ patches. This suggests that upon chain alignment, a hierarchical network forms that collectively stretches and induces nucleation in a precisely controlled way. Through the lens of polymer physics, we argue that if all chains would stretch to a similar extent, a clear correlation length of the stickers in the direction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…This implies an approximate equivalence between the strengths of monomer-monomer and monomersolvent interactions. Moreover, while it was not possible to observe the coil geometry by SAXS (or SANS [60]) at higher concentration (the interpretation of scattering data required non-overlapping coils), the configuration determined at low concentration was consistent with previous NMR results [46][47][48][49] and rheology [9,99,178], which demonstrated that the protein in NSF behaved as a typical polymer in solution, albeit slightly modified by its natural propensity to form transient 'sticky' ionic interactions [66,67]. (ii) Crucially, the combination of random coil geometry and uniform dynamics (from NMR studies [46][47][48][49]) implies similar levels of hydration across the entire fibroin coil, which precludes any explanation of gelation through interactions between hydrophobic regions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This implies an approximate equivalence between the strengths of monomer-monomer and monomersolvent interactions. Moreover, while it was not possible to observe the coil geometry by SAXS (or SANS [60]) at higher concentration (the interpretation of scattering data required non-overlapping coils), the configuration determined at low concentration was consistent with previous NMR results [46][47][48][49] and rheology [9,99,178], which demonstrated that the protein in NSF behaved as a typical polymer in solution, albeit slightly modified by its natural propensity to form transient 'sticky' ionic interactions [66,67]. (ii) Crucially, the combination of random coil geometry and uniform dynamics (from NMR studies [46][47][48][49]) implies similar levels of hydration across the entire fibroin coil, which precludes any explanation of gelation through interactions between hydrophobic regions.…”
Section: Discussionsupporting
confidence: 84%
“…These salts were selected because they lie towards the centre of the Hofmeister series [158][159][160][161][162] and are not expected to show any chemical affinity for the protein. In particular, monovalent cations avoid any possibility of bridging between carboxylate groups [65][66][67], which could affect aggregation and turbidity measurements. The turbidity is related to decreases in transmitted light, due to scattering from inhomogeneities in the dilute solution [98,100,[163][164][165][166][167].…”
Section: Cloud-point and Aggregation Measurements In Salt Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the highly concentrated silk solution contained in the middle silk glands has residues in energetically favored conformations close to average random coil values [ 39 , 40 ], but forms a hydrogen-bonded network that keeps it in a repeated type II β-turn structure [ 21 , 22 ]. These data and insights became the starting point to understand the molecular mechanisms behind the flow behavior generating the high-performance silk fibers from viewpoints of rheology [ 83 , 84 , 85 ].…”
Section: Silk I Structure Determined From Solution Nmrmentioning
confidence: 99%
“…The manufacturing of both natural and artificial polymer-based fibres relies on flowinduced crystallisation in non-linear rheological conditions [1][2][3][4][5]. The energy input required by this process may be significantly reduced through tailored macromolecular interactions, as exemplified by natural silk [6][7][8][9]: This protein, of which the conformation closely resembles a random coil [10], self-assembles in flow in aqueous conditions under energy requirements orders of magnitude lower than its synthetic counterparts [6]. It has been hypothesised that flow-induced stretching of the chain disrupts a solvation layer and in turn enables crystallisation to commence.…”
Section: Introductionmentioning
confidence: 99%